Randomisation in trials: do potential trial participants understand it and find it acceptable? - Kerr, C. (Journal of medical ethics, 2004)
Objective: To examine lay persons’ ability to identify methods of random allocation and their acceptability of using methods of random allocation in a clinical trial context. Design: Leaflets containing hypothetical medical, non-medical, and clinical trial scenarios involving random allocation, using material from guidelines for trial information leaflets. Setting and participants: Adults attending further education colleges (n = 130), covering a wide range of ages, occupations, and levels of education. Main measures: Judgements of whether each of five methods of allocation to two groups was random in a medical or non-medical scenario. Judgements of whether these allocation methods were acceptable in a randomised clinical trial scenario, with or without a scientific justification for randomisation. Results: The majority of our group of participants judged correctly that allowing people their preference was not random, and that the following were random: using a computer with no information about the individual (recommended wording for MREC trial leaflets), tossing a coin, drawing a name out of a hat. Judgements were split over allocating people in turn (not a random allocation method but shares features with randomisation). Judgements were no different in medical and non-medical scenarios. Few of the correctly identified random methods were judged to be acceptable in a clinical trial scenario. Inclusion of a scientific justification for randomising significantly increased the acceptability of only one random method: allocation by computer. Conclusions: Current UK guidelines’ recommended description of random allocation by computer seems warranted. However, while potential trial participants may understand what random allocation means, they may find it unacceptable unless offered an acceptable justification for its use.